Small-Molecule Inhibitors Overcome Epigenetic Reprogramming for Cancer Therapy - Xiao, Wenjing; Zhou, Qiaodan; Wen, Xudong; Wang, Rui; Liu, Ruijie; Wang, Tingting; Shi, Jianyou; Hu, Yonghe; Hou, Jun (Frontiers in Pharmacology, 2021)
Cancer treatment is a significant challenge for the global health system, although important pharmacological and therapeutic discoveries have been found. It has been widely established that cancer is associated with epigenetic modification. Because epigenetic modification is reversible, it has become an attractive target for drug development. Adding chemical groups to the DNA backbone and modifying histone proteins impart distinct characteristics on chromatin architecture. This process is mediated by various enzymes modifying chromatin structures to achieve the diversity of epigenetic space and the intricacy in gene expression files. After decades of effort, epigenetic modification represents the hallmarks of different types of cancer, and the enzymes involved in this process provide novel targets for anti-tumor therapy development. Epigenetic drugs have been shown promising results in both preclinical and clinical studies. The development and research of targets by epigenetic drugs provide a good direction for cancer therapy. Here, we have summarized the different types of epigenetic enzymes that target corresponding protein domains, emphasizing DNA methylation, histone modifications, and micro RNA-mediated cooperation with epigenetic modification, and highlighted recent achievements in developing targets for epigenetic inhibitor therapy. This article reviews current anti-cancer small molecule inhibitors targeting epigenetic modified enzymes and summarizes their performances in different stages of clinical trials. Future studies are needed to address their off-target effects and cytotoxicity to improve their clinical translation.